ROSELLE CALYX (HIBISCUS SABDARIFFA. L) AS AN ANTI-DIABETIC: ETHYL ACETATE FRACTION REDUCE FASTING BLOOD GLUCOSE TOTAL CHOLESTEROL AND REPAIR PANCREAS FUNCTION ON DIABETIC MODEL - SUHARTI, NETTY; ARMENIA, ARMENIA; ABDILLAH, RAHMAD; RAMADAN, CYNDI MURIA (International Journal of Applied Pharmaceutics, 2024)
Objective: In general, people with diabetes mellitus will experience disturbances in fat metabolism that lead to hypercholesterolemia. This study aims to determine the effect of ethyl acetate fraction hibiscus calyx on blood sugar, blood cholesterol level, and pancreas histology in diabetic Wistar Kyoto rats induced by streptozotocin. Methods: Thirty-six Wistar Kyoto rats were induced with intra-peritoneal streptozotocin at 55 mg/kg BW and stabilized for five days to obtain diabetic conditions. Diabetic animals were divided into four groups; the diabetic group was given vehicle, the glibenclamide group was given 0.45 mg/kg BW of Glibenclamide, and two groups were administered the ethyl acetate fraction of hibiscus calyxes (EAFHC) at doses of 100 mg/kg BW and 200 mg/kg BW for five days. Fasting blood sugar and lipids (total cholesterol and triglycerides) were measured on days 0, 1, 3, and 5. Pancreats were collected on days 1, 3 and 5 for weighing and histology examination. All data were analyzed using two-way ANOVA followed by the Duncan Multiple Rank Test (DMRT). Results: EAFHC significantly reduced fasting blood sugar and total cholesterol (p<0.05) but did not have a significant effect on triglycerides (p>0.05). Histology examination showed that EAFHC repaired pancreatic damage, as seen from the decrease in pancreatic histology scores (p<0.05), but the organ ratio did not show a significant improvement (p>0.1). Conclusion: This study revealed that EAFHC could be an alternative medicine in managing blood sugar levels and total cholesterol and improving pancreas function in associated models of diabetes mellitus hypercholesterolemia complications.